PERSEPSI DUKUNGAN ORGANISASI SEBAGAI MEDIATOR ANTARA KEADILAN ORGANISASI DAN KOMITMEN AFEKTIF PADA SEBUAH PERUSAHAAN DISTRIBUSI PELUMAS - Yoga Samudra Dewa; Alice Salendu (Universitas Mercu Buana, 2018)
Abstract. The aim of this research is to determine the role of perceived organizational support as mediator variable between organizational justice dan affective commitment in Shell lubricants distributor company in Indonesia. The respondents of this study are 52 employees which completing the questionnaire through online and dirrect response. This study used a quantitative research design with mediation analysis from Hayes in PROCESS SPSS version 25. The results showed that the perceived organizational support mediated with BootLLCI value = 0.016 and BootULCI = 0.265, which mean perceived organization support is fully mediated in the relationship between organizational justice and affective commitment. In order to get optimized perceived organizational support from the employee, the organization should treat the employee fairly, as the result, it will increase employee`s affective commitment and the organization performance.